Young Entrepreneurs in Sub-Saharan Africa - Dawa, Samuel (Routledge, 2017)
Young people are highly visible throughout urban and rural areas of sub-Saharan Africa, engaging in a wide range of income-generating activities. Young women operating from open-sided shacks or tabletops can be seen selling a range of goods from fruit and vegetables to cosmetics, and offering services such as plaiting hair and sewing clothes. Young men more commonly deal in manufactured goods, including electronic gadgets, and offer services such as car washing and charging mobile phones, though they are also increasingly entering into former female domains (Overå, 2007). These young people are predominant among the “ordinary” entrepreneurs of the global South (Jeffrey & Dyson, 2013) proving themselves skilful at finding economic niches, managing scarce resources, and seizing profitable opportunities within constrained economic environments. Economic restructuring and the transformation of labour markets have resulted in limited employment opportunities for young people whose unemployment rates can be two to three times higher than the norm (World Bank, 2012). Young people are often depicted as having become increasingly marginalised, causing idleness and frustration which, it is believed, can lead to involvement in crime, organised violence, and protests (Garcia & Fares, 2008; World Bank, 2006, 2012).1 Consequently, entrepreneurship is increasingly being promoted as a key tool to combat the youth unemployment crisis and as one of the main drivers of economic and social transformation in sub-Saharan Africa (Africa Commission, 2009; World Bank, 2006). In light of their limited possibilities to gain formal sector jobs in the public or private sector, young people are being encouraged to be “job creators” rather than “job seekers”, thus becoming self-employed “entrepreneurs” (Langevang & Gough, 2012).